Volume 8: Polar and Arctic Sciences and Technology; Petroleum Technology 2016
DOI: 10.1115/omae2016-54450
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nano-Silicon Dioxide (SiO2) on Polymer/Salt Treated Bentonite Drilling Fluid Systems

Abstract: Recently the application of nanomaterial is attracting the oil and gas industry. The preliminary nanomaterials research results show an improving performance of cement, drilling fluid and Enhanced Oil Recovery. In this paper, the effect of nano Silicon dioxide (SiO2) on polymer (HV-CMC, Xanthan gum, LV-CMC) and salt (KCl, NaCl) treated bentonite drilling fluid systems has been studied at room temperature. The results show that the performance of nano SiO2 in bentonite mud system d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Belayneh et al [29] focused on the effect of nano-silicon dioxide (SiO 2 ) on polymer (HV-CMC, LV-CMC, xanthan gum) and salt (KCl, NaCl) treated bentonite drilling fluid systems. They developed a reference fluid containing 0.2 g low viscosity (LV)-carboxymethyl cellulose (CMC) and 0.3 g xanthan gum polymers in 25 g bentonite/500 g water with 2.5 g KCl.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Belayneh et al [29] focused on the effect of nano-silicon dioxide (SiO 2 ) on polymer (HV-CMC, LV-CMC, xanthan gum) and salt (KCl, NaCl) treated bentonite drilling fluid systems. They developed a reference fluid containing 0.2 g low viscosity (LV)-carboxymethyl cellulose (CMC) and 0.3 g xanthan gum polymers in 25 g bentonite/500 g water with 2.5 g KCl.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Reports have shown that the smaller the nanoparticle, the greater the increased viscosity and shear stress [ 10 , 11 ], while in other cases, nanoparticles were added to WBM to increase shear thinning behavior. Especially shear thinning behaviors of drilling mud when TiO 2 is added are shown linearly with increasing TiO 2 addition [ 12 , 13 , 14 , 15 , 16 ]. In drilling operations, fluid loss caused by penetration of drilling mud into the reservoir gap has been reduced by adding nanoparticles; in one case, the necessary thickness of the filter cake was reduced by adding two-dimensional, Graphene oxide (GO) particles, which led to reduced fluid loss through raised filter cake impermeability.…”
Section: Introductionmentioning
confidence: 99%
“…At present possible applications of nanofluids are very actively investigated [8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The most important of these are viscosity and rheology because they influence the pressure loss during flushing-out of the well, the efficiency of the cutting transport, the borehole stability, etc. In this regard, a large number of investigations of the nanoparticles effect on the viscosity and rheological behaviour of the drilling muds have been carried out in the last few years [8][9][10][11][12][13][14][15][16][17][18]. It was found that nanoparticles significantly increase the viscosity of drilling fluids, and change the rheological properties of these solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation